Optimisation of spray drying conditions of boiling extract liquid of P. Amboinicus Lour for maximum antioxidant activity - Mohd Shaiful Azman Abdul Rahim; Shamsul Muhamad; Siti Fatimah Zahrah Mat Ali; Jailani Salihon; Mashitah Mohd Yusoff (2014)
Optimisation of spray drying of boiling extract liquid of P. amboinicus Lour. encapsulated in maltodextrin for maximum antioxidant activity was conducted using response surface methodology comprising of 22 factorial experiments followed by the steepest ascent method. Fresh samples of P. amboinicus Lour. were randomly collected from Kuantan, Malaysia. The antioxidant activities of spray dried boiling extract encapsulated in maltodextrin were assessed using the 1,1-diphenyl-2- picrylhydrazyl (DPPH) free radical scavenging assay. Objective: The objective was to optimize the spray drying of the boiling extract liquid of P. amboinicus Lour. plant, for maximum antioxidant activity. Results: The results showed that the highest yield of antioxidant activity of spray dried boiling extract was obtained when the spray dryer was operated at the combination of levels of operational variables X1 (temperature) = 177.65oC and X2 (concentration of maltodextrin) = 48.65%. Conclusion: These findings may have a bearing on the application of spray drying technology in preparing herbal extracts, and may prove useful to the herbs industries.